2023
DOI: 10.1021/acsptsci.3c00046
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of 22-(4′-Pyridinecarbonyl) Jorunnamycin A against Lung Cancer Cell Invasion and Angiogenesis via AKT/mTOR Signaling

Abstract: Non-small-cell lung cancer (NSCLC), the most prevalent form of lung cancer, is associated with an unfavorable prognosis owing to its high rate of metastasis. Thus, the identification of new drugs with potent anticancer activities is essential to improve the clinical outcome of this disease. Marine organisms exhibit a diverse source of biologically active compounds with anticancer effects. The anticancer effects of jorunnamycin A (JA) derived from the Thai blue sponge (Xestospongia sp.) and 22-(4′-pyridinecarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…22-(4′-pyridinecarbonyl) jorunnamycin A (22-(4′-py)-JA) ( 4 ) is a synthetic derivative of jorunnamycin A ( 3 ) isolated from Xestospongia sp. [ 16 , 17 ]. This compound demonstrated robust cytotoxic efficacy in the nanomolar range, exerting an apoptosis-inducing effect on H460, H292, and A549 NSCLC cell lines through an ERK/MEK/Bcl-2-dependent mechanism [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…22-(4′-pyridinecarbonyl) jorunnamycin A (22-(4′-py)-JA) ( 4 ) is a synthetic derivative of jorunnamycin A ( 3 ) isolated from Xestospongia sp. [ 16 , 17 ]. This compound demonstrated robust cytotoxic efficacy in the nanomolar range, exerting an apoptosis-inducing effect on H460, H292, and A549 NSCLC cell lines through an ERK/MEK/Bcl-2-dependent mechanism [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro assays demonstrated that inhibition of AKT/mTOR/P70S6K signaling pathway by 22-(4′-py)-JA resulted in the attenuation of matrix metalloproteinases (MMP-2 and MMP-9), hypoxia-inducible factor-1α (HIF-1α), and vascular endothelial growth factor (VEGF). In vivo assays involving intravenous inoculation of the A549 cell line in mice revealed that the group treated with 22-(4′-py)-JA ( 4 ) exhibited a reduction in pulmonary nodules, thereby mitigating the metastatic progression [ 17 ]. Cell invasion and angiogenesis processes are related to the spread of tumor cells, leading to metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations